2020
DOI: 10.3390/s20174680
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Nonlinear Equalizers for 112-Gbps Optical Interconnects: Efficiency and Stability

Abstract: Low-complexity nonlinear equalization is critical for reliable high-speed short-reach optical interconnects. In this paper, we compare the complexity, efficiency and stability performance of pruned Volterra series-based equalization (VE) and neural network-based equalization (NNE) for 112 Gbps vertical cavity surface emitting laser (VCSEL) enabled optical interconnects. The design space of nonlinear equalizers and their pruning algorithms are carefully investigated to reveal fundamental reasons of powerful non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In contrast, the activation function in the output layer is application specific. In the context of IM/DD systems, the authors in [18], use a multilayer perceptron (MLP) for Rx nonlinear equalization, with multiple hidden layers and an output layer. The authors considered the rectified linear unit ReLU(x) , hyperbolic tangent tanh(x) and sigmoid σ(x) activation functions for the hidden layers, while a softmax(x) function is used to convert the results of output layer to probability distribution for each level of the PAM signal [18].…”
Section: Nonlinear Equalization At the Rxmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the activation function in the output layer is application specific. In the context of IM/DD systems, the authors in [18], use a multilayer perceptron (MLP) for Rx nonlinear equalization, with multiple hidden layers and an output layer. The authors considered the rectified linear unit ReLU(x) , hyperbolic tangent tanh(x) and sigmoid σ(x) activation functions for the hidden layers, while a softmax(x) function is used to convert the results of output layer to probability distribution for each level of the PAM signal [18].…”
Section: Nonlinear Equalization At the Rxmentioning
confidence: 99%
“…In the context of IM/DD systems, the authors in [18], use a multilayer perceptron (MLP) for Rx nonlinear equalization, with multiple hidden layers and an output layer. The authors considered the rectified linear unit ReLU(x) , hyperbolic tangent tanh(x) and sigmoid σ(x) activation functions for the hidden layers, while a softmax(x) function is used to convert the results of output layer to probability distribution for each level of the PAM signal [18]. In the absence of hidden layers, and exhibiting a single neuron structure, as with the FLNN proposed in this article, the activation function can only be confined to the FLNN output.…”
Section: Nonlinear Equalization At the Rxmentioning
confidence: 99%
See 1 more Smart Citation
“…The fast development of OWPT technology is attributed not only to the innovations of systemlevel design, but also to various key devices, such as semiconductor lasers and photovoltaic (PV) cells [12], [13]. In the recent years, high efficient semiconductor lasers have been widely used in the fields of high-speed communications and intelligent manufacturing [13], [14]. The electrooptical conversion efficiency have reached 68% for the continuous-wave 100 W-class 808 nm laser diode arrays [13].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed free-space optics communication system used a dual electro-optical modulator design, which could improve the transmission rate. For direct-detection optical communication systems, Zhang, W. et al compared the complexity, efficiency, and stability performance of pruned Volterra series-based equalization (VE) and neural network-based equalization (NNE) for 112 Gbps vertical-cavity surface-emitting laser (VCSEL)-enabled optical interconnects [ 8 ]. The experimental results showed that NNE has more than one order of magnitude bit error rate (BER) advantage over VE at the same computation complexity, and pruned NNE has around 50% lower computation complexity compared to VE at the same BER level.…”
mentioning
confidence: 99%